2011
DOI: 10.1177/193229681100500510
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Microdialysis as a Method for Measuring Glucose and Lactate during and after Cardiac Surgery

Abstract: Background: The aim was to evaluate intravascular microdialysis as a method for measuring blood glucose and lactate in a clinical setting during and after cardiac surgery. Methods: Ten patients undergoing cardiac surgery were included. A microdialysis catheter was percutaneously placed in the superior vena cava or right atrium. Glucose and lactate values measured by the microdialysis technique were analyzed and compared with reference methods, i.e., arterial and venous blood gas values, once every hour up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
11
1
1
Order By: Relevance
“…studied the correlation between central venous and arterial lactate values and observed a mean difference of 0.03 mmol/L ( r  = 0.996) [23]. In our previous study, we also found good agreement between arterial and venous blood gas lactate values (mean difference = 0.09 mmol/L, limit of agreement ±0.6 mmol/L and Pearson correlation coefficient = 0.92), further supporting arterial blood gas as a reference method [17]. …”
Section: Discussionsupporting
confidence: 69%
“…studied the correlation between central venous and arterial lactate values and observed a mean difference of 0.03 mmol/L ( r  = 0.996) [23]. In our previous study, we also found good agreement between arterial and venous blood gas lactate values (mean difference = 0.09 mmol/L, limit of agreement ±0.6 mmol/L and Pearson correlation coefficient = 0.92), further supporting arterial blood gas as a reference method [17]. …”
Section: Discussionsupporting
confidence: 69%
“…Although the Clarke-Error grid is developed for point-of-care glucose analysers for diabetic patients [20], it may serve as a risk estimator. Similar results were recently obtained in conjunction with cardiac surgery using a similar intravascular microdialysis catheter but the analyses were not performed using the on-line measurements [21]. …”
Section: Discussionsupporting
confidence: 62%
“…25 Thus, Möller et al found good agreement between arterial and venous blood gas lactate values (mean difference = 0.09 mmol L -1 , limits of agreement ± 0.6 mmol L -1 , r = 0.92), also supporting arterial blood gases as a reference method. 26 Higher limits of agreement between Lactate cont and Lactate art in our study can be explained by the increased lactate values and variations in lactate postoperatively in highrisk cardiac patients. In addition, as the Eirus TM system reflects the blood lactate concentrations approximately five minutes later compared to blood gases, a slight mismatch between the methods may occur which was observed both in our study and in other investigations.…”
Section: Discussionmentioning
confidence: 77%